Analysing common mistakes in translations of tourist texts (Spanish, English and German) - Durán Muñoz, Isabel (Onomázein, 2012)
Translation in the tourist sector has received little attention in the academic context of specialized translation, despite the importance of translation mediating between local and foreign cultures and the meaningful role for the economy in some countries like Spain. in this context, this paper intends to emphasize the relevance of translation in the tourist sector and, in turn, to analyse the common features and mistakes that are frequently encountered in tourist texts involving Spanish, english and German language. Likewise, it proposes a series of possible solutions to improve the quality of this kind of specialized translations and, thus, to ensure a good relationship between source and target cultures.